In-silico optimisation of ICD defibrillation efficacy by modifying lead/can configurations using a cohort of high-resolution whole-torso heart models. (19th May 2022) - Qian, S; Monaci, S; Mendonca-Costa, C; Campos, F; Gemmell, P; Zaidi, S; Rajani, R; Whitaker, J; Rinaldi, C; Bishop, M
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Medical Research Council, UK Background: ICD is an effective direct therapy against VT/VF by applying a strong electrical shock across the heart between the shocking coil and can. Conventionally, patients will have a shocking coil inside the right ventricle (RV) and a can at the upper left chest. However, due to infections or other conditions, the can may need to place towards the right chest. The placement of the RV coil may also vary in different cases, for example avoiding scar. However, it is unclear how defibrillation efficacy may be altered by these unavoidable modifications to conventional lead/can configurations and whether optimisation may be possible. Purpose: To compare defibrillation efficacy of modifications of ICD configurations in a cohort of whole-torso models. Methods: A cohort of 15 whole torso models was generated from high resolution CT data and contrast CT cardiac scans, including 5 dilated cardiomyopathy (DCM), 5 hypertrophic cardiomyopathy (HCM) and 5 structurally normal patients (Fig A). Transvenous ICDs were represented by a shocking coil inside the RV (near apex) and a (ground) can at the upper left chest as default settings. Configurations were then varied by moving the can to the right chest, moving the RV coil up the mid-septum or adding extra grounds (Superior Vena Cava (SVC) coil, coronary sinus (CS) coil (Fig A)). Defibrillation-strength shocks were applied to all models (Fig B). DFTs and mean electrical field were evaluated across the whole heart as well as specific LV, RV, RV insertion regions, along with overall impedance. Results: Shifting the can from left to right significantly increased DFT for the whole heart (23 J vs 15 J, P=0.03) and LV (25 J vs 17 J, P=0.03) (Fig C) and reduced the mean electrical field. Moving the RV coil further up the septum did not significantly alter DFT (Fig D), but did reduce mean electrical field for all regions and reduce impedance significantly. Additional separate coils significantly reduced DFT for all regions (Fig D) by increasing mean electrical field, whilst adding both coils significantly reduced DFT the most (whole heart: 15 J vs 6 J, P=0.03) (Fig E). Impedance was increased significantly by adding SVC coil, but reduced significantly by adding CS coil. Adding both coils increased impedance slightly. Conclusions: Although a right-sided can increases DFT by over 50%, additional leads (grounds) may mitigate this increase by increasing mean electrical field. Moving the RV coil closer to the mid-septum reduces DFT slightly, but also reduces mean electrical field and impedance significantly.